Mechanical properties of sedge fiber-reinforced epoxy composites incorporated with graphene oxide - Lucas de Mendonça Neuba; Thuane Teixeira Silva; Lucas Montenegro Reis; Sergio Neves Monteiro; Noan Tonini Simonassi; Luís Cláudio Candido; Artur Camposo Pereira (Journal of Materials Research and Technology, 2025)
Lighter composite materials, especially those with a fiber-reinforced polymeric matrix are well fit in the current needs to combine low density material and high mechanical resistance. This effort led to several studies focused on incorporating lignocellulosic natural fibers (FNLs) into polymeric matrices. In this context, the present study suggested using sedge fibers (Cyperus malaccensis) as reinforcement in an epoxy matrix composite incorporated with graphene oxide (GO). The mechanical properties were evaluated through tensile, Izod and Charpy impact, bending and compressing tests. Morphological analyses of composites reinforced with sedge fibers were conducted to examine fracture surfaces after the tests. The results disclosed a significant difference when the GO was incorporated into the epoxy matrix. For instance, the group disclosing the best performance in the Izod and Charpy Impact tests revealed values of 108.5 ± 12.22 and 155.51 ± 17.05 J/m, respectively. SEM micrographs revealed that some agglomerations of the GO nano-reinforcement, and interface delamination were drastically reduced, indicating a stronger interface.